Politik Kekerabatan dalam Pemilihan Kepala Desa di Desa Dolog Huluan Kabupaten Simalungun - Asha Yatri Saragih; Julia Ivanna (Departement of Mathematics Education, 2024)
Kinship politics is a political strategy that uses family relationships and kinship ties to establish power and strengthen political positions. The kinship in question includes family members, blood relations, marriage relations and extensions such as tribe and clan. This research focuses on the role of kinship in the election of village heads in Dolog Huluan Village. This research uses a qualitative research method with a qualitative descriptive approach which aims to collect, analyze and interpret data in the form of words, actions or symbols in the form of narratives, interviews, observations or documents to produce in-depth knowledge and understanding regarding the role of kinship in the election of heads. village. It is hoped that this research can provide awareness to the public that kinship politics has a negative influence even though in the end kinship politics is valid and acceptable. The results of the analysis reveal that in Dolog Huluan Village there is still kinship politics that occurs during the election of the village head, which essentially has a huge influence on the clan.